Significant Performance and Stability Improvements of Low-Temperature IGZO TFTs by the Formation of In-F Nanoparticles on an SiO2 Buffer Layer - Ho-young Jeong; Seung-hee Nam; Kwon-shik Park; Soo-young Yoon; Chanju Park; Jin Jang (Nanomaterials, 2020)
We report the performance improvement of low-temperature coplanar indium–gallium–zinc–oxide (IGZO) thin-film transistors (TFTs) with a maximum process temperature of 230 °C. We treated F plasma on the surface of an SiO2 buffer layer before depositing the IGZO semiconductor by reactive sputtering. The field-effect mobility increases from 3.8 to 9.0 cm2 V−1·s−1, and the threshold voltage shift (ΔVth) under positive-bias temperature stress decreases from 3.2 to 0.2 V by F-plasma exposure. High-resolution transmission electron microscopy and atom probe tomography analysis reveal that indium fluoride (In-F) nanoparticles are formed at the IGZO/buffer layer interface. This increases the density of the IGZO and improves the TFT performance as well as its bias stability. The results can be applied to the manufacturing of low-temperature coplanar oxide TFTs for oxide electronics, including information displays.